2022
DOI: 10.3390/atmos13060891
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Human Cognitive Abilities with Elevated Carbon Dioxide Concentrations in an Enclosed Chamber

Abstract: Fifteen participants were exposed in an enclosed environmental chamber to investigate the effects of elevated carbon dioxide (CO2) concentration on their cognitive abilities. Three CO2 conditions (1500, 3500, and 5000 ppm) were achieved by constant air supply and additional ultrapure CO2. All participants received the same exposure under each condition, during which they performed six cognitive tests evaluating human perception, attention, short-term working memory, risky decision-making, and executive ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Generalized additive mixed effect model (GAMM) analyses [47,48,55,56] and the correlation analyses were performed using the open-source statistical package R version 3.6.1 (R Project for Statistical Computing, Vienna, Austria) to test the relationships between noise exposures and performance metrics, treating the subject as a random effect. In addition, the PLS-SEM method was used with the SmartPLS 3.0 software (SmartPLS GmbH, Bönningstedt, Germany) to explore the underlying mechanism of noise effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generalized additive mixed effect model (GAMM) analyses [47,48,55,56] and the correlation analyses were performed using the open-source statistical package R version 3.6.1 (R Project for Statistical Computing, Vienna, Austria) to test the relationships between noise exposures and performance metrics, treating the subject as a random effect. In addition, the PLS-SEM method was used with the SmartPLS 3.0 software (SmartPLS GmbH, Bönningstedt, Germany) to explore the underlying mechanism of noise effects.…”
Section: Discussionmentioning
confidence: 99%
“…Seven computer-based cognitive tests, summarized in Table 2, were adopted based on the information-processing of the human mind [48]. The details are described as follows.…”
Section: Cognitive Performancementioning
confidence: 99%
“…Response speed was widely used in previous studies as one of the key parameters to measure people's cognitive performance. Among the studies which found significant effects of CO2 on cognitive performance, some did not find significant effects of exposures to elevated CO2 levels on response speed [17], [18], some studies found that response speed significantly increased in some cognitive tasks under higher concentrations [20], and some showed decreased response speed under higher CO2 levels [6]- [8], [13], [21].…”
Section: Introductionmentioning
confidence: 99%